Emotionally-oriented design in museums: a case study of the Jewish Museum Berlin - Zhang, Zhihui; Lu, Jing; Zhang, Xiuying (Frontiers in Psychology, 2024)
Objective: This study examines the intricate interplay between architectural design and visitor emotional responses at the Jewish Museum Berlin, focusing on how specific spatial elements such as the Holocaust Tower, Garden of Exile, The Voids, and The Axis elicit varied affective experiences. The research aims to extend the discourse on environmental psychology and architectural empathy, particularly within the context of memorial museums.Method: Employing a non-intrusive approach, the study gathered emotional response data using the Positive and Negative Affect Schedule (PANAS) from 113 museum visitors, with 102 valid responses analyzed. Environmental conditions such as light, sound, and spatial design were quantitatively measured to correlate with emotional responses captured at the end of visitors' tours across the designated museum spaces.Results: Findings revealed that architectural elements significantly influence emotional responses. High levels of negative emotions like fear and anxiety were markedly evident in the Holocaust Tower due to its minimal lighting and stark concrete structure. Conversely, the Garden of Exile induced more positive emotions through its use of natural light and greenery, emphasizing the role of biophilic design in enhancing emotional well-being. Statistical analysis supported these observations, with variations in emotional impact across different spaces demonstrating the profound effect of architectural design on visitor experiences.This study confirms that a variety of design elements and spatial strategies not only facilitate the presentation of historical narratives but also actively sculpt the emotional involvement and experiences of visitors.